2013
DOI: 10.4038/jas.v8i1.5375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic and inorganic fertilizers on biomass production, oil yield and quality of vetiver (Vetiveria zizanioides l.)

Abstract: to find out most suitable fertilizer combination for higher growth, yield and quality of Vetiver. Different proportions of organic and inorganic fertilizers such as inorganic fertilizer alone, compost: inorganic fertilizer (1:3), compost: inorganic fertilizer (1:1), compost: inorganic fertilizer (3:1), compost alone and control (top soil: sand-1:2) were used as treatments. Growth, yield, oil content and quality parameters were taken 9 months after planting. Compost: inorganic fertilizer (3:1) mixture showed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
10
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 5 publications
6
10
2
Order By: Relevance
“…The application of small amount of compost with or without inorganic fertilizer had a significant effect on plant biomass. The same results were obtained by Priyadarshani et al (2013) who revealed optimal production of vetiver biomass following application of a mixture of compost with inorganic fertilizer in a 3:1 ratio. Rotkittikhun et al (2007) demonstrated the suitability of compost application with lower doses of inorganic fertilizer for higher biomass production in field crops such as lemongrass and sunflower.…”
Section: Impact Of Different Amendments Formulation On Biomass Of M supporting
confidence: 81%
“…The application of small amount of compost with or without inorganic fertilizer had a significant effect on plant biomass. The same results were obtained by Priyadarshani et al (2013) who revealed optimal production of vetiver biomass following application of a mixture of compost with inorganic fertilizer in a 3:1 ratio. Rotkittikhun et al (2007) demonstrated the suitability of compost application with lower doses of inorganic fertilizer for higher biomass production in field crops such as lemongrass and sunflower.…”
Section: Impact Of Different Amendments Formulation On Biomass Of M supporting
confidence: 81%
“…However, no significant differences (p>0.05) was noted at 6 th week after planting. In contrast to this study, Priyadarshani et al (2013) stated that both compost and inorganic fertilizer treatments had significant effect on the shoot and root dry weights.…”
Section: Dry Weight Of Leavescontrasting
confidence: 96%
“…The effect of the compost in the presence of lime improves the soil with respect to pH, conductivity, the content of organic matter and the supply of adequate nutrients for better growth and yield (Priyadarshani et al, 2013). Al-Fraihat et al (2011) confirmed that the effect of organic fertilizer improves the physical, chemical and biological properties of soils, increasing their cation exchange capacity and water retention, resulting in better plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…influence of organic fertilization on the content of essential oil can be variable between species for example, Priyadarshani et al (2013) observed that higher oil content (3.74%) was recorded in Vetiveria zizanioides planted with 75% of organic and 25% inorganic fertilizer. The leaf oil yield of M. arvensis was positively influenced by organic fertilizer as same as reported by Chagas et al (2011), with same species and with Ocimum selloi fertilized with cattle manure compost (Costa et al, 2008).…”
Section: Constituentsmentioning
confidence: 99%
See 1 more Smart Citation